TINJAUAN WARNA PADA VISUAL BRANDING WARUNG KOPI LOKAL - Novena Ulita (Universitas Trisakti, 2019)
AbstractColor Overview on Visual Branding Local Coffee Shop. Visual power is an important part of marketing strategies. Visually gives a tremendous influence on consumer purchasing decisions. Humans have a direct reaction to color and shape to improve memory of vision, recognize, and identify brands. Color can convey messages and give special reactions to the human brain. The phenomenon of drinking coffee in coffee shopsis now shifting in the community. This research uses netnographic methods related to the existence and phenomenon of local coffee shops. By taking advantage in big data that can be accessed online, visual data analyzed with color branding theory, visual branding theory and sensory branding theory. The results of this study showed the increase of the local coffee shops presence in digital information media, and the tendency of certainform, color and brand names using local term to put forward Indonesia local identity. AbstrakTinjauan Warna pada Visual Branding Warung Kopi Lokal. Kekuatan visual menjadi bagian penting dalam strategi pemasaran. Visual memberikan pengaruh luar biasa terhadap keputusan pembelian konsumen. Manusia memiliki reaksi langsung terhadap warna dan bentuk, meningkatkan memori penglihatan, mengenali, dan mengidentifikasi brand. Warna dapat menyampaikan pesan dan memberikan reaksi khusus pada otakmanusia. Fenomena minum kopi di warung kopi saat ini sudah bergeser di masyarakat. Penelitian ini menggunakan metode netnografi terkait keberadaan dan fenomena warung kopi lokal. Dengan memanfaatkan big data yang dapat diakses secara online, data visual dianalisi menggunakan teori color branding, teori visual branding dan teori branding sensory. Hasil penelitian menunjukkan adanya peningkatan keberadaan warung kopilokal pada media informasi digital, serta kecenderungan penggunaan bentuk, warna serta penggunaan istilah lokal untuk mengedepankan identitas lokal Indonesia.